2020
DOI: 10.1002/hbm.25221
|View full text |Cite
|
Sign up to set email alerts
|

Altered thalamic connectivity in insomnia disorder during wakefulness and sleep

Abstract: Insomnia disorder is the most common sleep disorder and has drawn increasing attention. Many studies have shown that hyperarousal plays a key role in the pathophysiology of insomnia disorder. However, the specific brain mechanisms underlying insomnia disorder remain unclear. To elucidate the neuropathophysiology of insomnia disorder, we investigated the brain functional networks of patients with insomnia disorder and healthy controls across the sleep-wake cycle. EEG-fMRI data from 33 patients with insomnia dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…The study on sleep deprivation revealed increased thalamic activation after total sleep deprivation, which suggested that increased thalamic activation may compensate for the attention in order to complete the task (30). Notably, the more positive connectivity between the thalamus and cortical regions in patients with insomnia was found in comparison with the healthy controls, which also supported the hyperarousal hypothesis (31). In conclusion, these explorative findings may explain the structural connectivity mechanisms underlying the reduced alertness and executive function in patients with SWD.…”
Section: Discussionmentioning
confidence: 63%
“…The study on sleep deprivation revealed increased thalamic activation after total sleep deprivation, which suggested that increased thalamic activation may compensate for the attention in order to complete the task (30). Notably, the more positive connectivity between the thalamus and cortical regions in patients with insomnia was found in comparison with the healthy controls, which also supported the hyperarousal hypothesis (31). In conclusion, these explorative findings may explain the structural connectivity mechanisms underlying the reduced alertness and executive function in patients with SWD.…”
Section: Discussionmentioning
confidence: 63%
“…Although the mechanism by which subcortical areas, such as the putamen, regulate arousal is still poorly understood, the dysfunction of the frontostriatal circuit seems to have a role in insomnia. In this line, prior functional MRI studies have reported altered patterns of connectivity between subcortical (putamen) and cortical (frontal) regions in insomnia patients [ 52 54 ]. We found no relationship, however, with thalamic volumes.…”
Section: Discussionmentioning
confidence: 94%
“…The program 3dLMEr implemented in AFNI was employed to build the statistical model and perform the linear mixed-effect analysis (Chen, Saad, Britton, Pine, & Cox, 2013) (https://afni.nimh.nih.gov/ pub/dist/doc/htmldoc/programs/3dLMEr_sphx.html#ahelp-3dlmer) because of its advantages in handling unbalanced data and controlling for potential nestedness (Zou et al, 2021). The model included variates of stages, epochs, average FD, age, sex, and years of education.…”
Section: Discussionmentioning
confidence: 99%